Factors and criteria influencing the success of sustainable buildings in Hong Kong. Issue 1 (14th February 2019) - Tang, Ziwei; Ng, Shiu-tong Thomas; Skitmore, Martin
Abstract : The success of sustainable buildings can help ease the adverse impact of climate change. For this reason, sustainable buildings are becoming a worldwide trend. While defining both critical success factors and success criteria is a prerequisite for achieving sustainable building success, very few studies have been conducted to identify the factors and criteria influencing the success of sustainable buildings. In this study, the structured questionnaire survey method was applied to identify the critical success factors for procuring sustainable building projects and success criteria for measuring the success of sustainable building projects in Hong Kong, China. The results show that top success criteria for sustainable buildings can be grouped into 'success of traditional project performance'; 'success of sustainability performance from an environmental, social and economic perspective'; and 'participants' satisfaction'. Meanwhile, a factor analysis reveals five principal component factor groups as 'top management and team competence'; 'project performance, continuous improvement and stakeholder benefits effectiveness'; 'life-cycle process management effectiveness'; 'integrated design and resource management effectiveness'; and 'budget and risk control effectiveness'. The findings of this paper should help improve understanding of the criteria for measuring sustainable building success and the critical factors leading to the success of these criteria.